Lightweight framework for quality assurance in SMEs - Schapiro, Ariel (2011)
Based on their business needs, many software Small and Medium Enterprises (SMEs) differentiate through the high quality of their deliverables, compliancy with standards and alignment with engineering best practices. This paper explains how an SME in that context, successfully used a lightweight framework based on premises like self-assessment, tailoring, automation and positive peer pressure that assured a high level of service quality while removing the implied costs that would be derived from implementing a Quality Assurance (QA) department. Theframework aligned with the company’s agile processes allowing teams, through the implementation of short iterations, to assess their compliancy with a tailored quality baseline and make reviews with the help of cross-teams QualityReviewers. The result was a low cost framework that helped to grow factors like overall process quality while increasing quality perceived from the customer.